1982
DOI: 10.1111/j.1600-0773.1982.tb00985.x
|View full text |Cite
|
Sign up to set email alerts
|

Dextran‐Induced Lowering of Plasminogen Proactivator and Functionally Active High Molecular Weight Kininogen in the Rat

Abstract: Incubation of plasminogen-free rat citrated plasma with acetone (23 % v/v) yielded enzyme preparations with high levels of plasminogen activator (PGA) and kininogenase (kallikrein), but with a low concentration of high molecular weight kininogen (HMWK) active as cofactor for kaolin-induced activation of factor XII. When benzamidine (4.0 mM) was present during acetone activation, a high yield of functionally active HMWK was obtained. Gel chromatography separated PGA into one high molecular weight fraction (HMW-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

1982
1982
1984
1984

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…In accordance with previous results (Briseid & Berstad 1981;Berstad & Briseid 1982;Berstad 1982) we found in the present work that clinical dextran (HMr dextran) injected intravenously into rats rapidly lowered the plasma level of pro-PGA, as well as the capacity of HMrK to function as a cofactor in the kaolin induced activation of factor XII. These events took place at a point in time prior to a heavy fall in blood pressure.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In accordance with previous results (Briseid & Berstad 1981;Berstad & Briseid 1982;Berstad 1982) we found in the present work that clinical dextran (HMr dextran) injected intravenously into rats rapidly lowered the plasma level of pro-PGA, as well as the capacity of HMrK to function as a cofactor in the kaolin induced activation of factor XII. These events took place at a point in time prior to a heavy fall in blood pressure.…”
Section: Discussionsupporting
confidence: 94%
“…40 mg/kg. In accordance with previous works (Briseid & Berstad 198 I ;Berstad & Briseid 1982;Berstad 1982) it was found that the intravenous injection of HMr dextran lowered the plasma levels of plasminogen proactivator (pro-PGA) and functionally active high molecular weight kininogen (HMrK). Also LMr dextran, 200 mg/kg, induced significant reductions in the mentioned parameters, but less extensive than those obtained by HMrdextran, 40 mg/kg, and pretreatment ofthe rats with LMr dextran inhibited the subsequent effects of HMr dextran.…”
supporting
confidence: 90%
See 3 more Smart Citations